Kinematic analysis of support phase characteristics in women race walking - Bej, D. K. (American Journal of Sports Science, 2020)
Race walking requires a great deal of effort to compete successfully which includes a unique combination of technique, extreme physical exertion and mental focus. Unlike running, race walking is composed by support phase (heel strike, mid-stance and toe off) and swing phase. The aim of this study was to analyze the association between different kinematic characteristics of support phase during race walking and walking velocity. The rules of race walking demand that no visible flight time should occur and the stance leg must be straightened from initial contact to midstance. Previous research has not examined whether these rules also have an effect on walking performance and what consequences might arise. Top ten (U-20 Girls) finishers of 10000m race walk discipline, 33rd National Junior Athletic Championships, 2017 held at Acharya Nagarjuna University, Vijaywada, A. P. India were recorded by using two Nikon digital 4K camcorders (60 Hz) mounted on rigid tripods were placed alongside of the course at approximately 90° to the plane of motion. The junior athletes were analyzed by using motion analysis software (KINOVEA 0.8.27). Descriptive statistics and Pearson Product Moment Correlation coefficient (p<0.05) were employed for statistical calculation.